2020
DOI: 10.1038/s41419-020-2699-2
|View full text |Cite
|
Sign up to set email alerts
|

SPEN induces miR-4652-3p to target HIPK2 in nasopharyngeal carcinoma

Abstract: SPEN family transcriptional repressor (SPEN), also known as the SMART/HDAC1-associated repressor protein (SHARP), has been reported to modulate the malignant phenotypes of breast cancer, colon cancer, and ovarian cancer. However, its role and the detail molecular basis in nasopharyngeal carcinoma (NPC) remain elusive. In this study, the SPEN mRNA and protein expression was found to be increased in NPC cells and tissues compared with nonmalignant nasopharyngeal epithelial cells and tissues. Elevated SPEN protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Finally, the current study sought to define the underlying mechanism of the effect of gal-3 on NPC cells. The activation of the ERK1/2 and Akt signaling pathways is involved in the proliferation, migration, invasion, metastasis and radiosensitivity of NPC (38)(39)(40). However, whether gal-3 affects the ERK1/2 and Akt signaling pathways of NPC cell lines remains unknown.…”
Section: Expression Levels Of Gal-3 ---------------------------------mentioning
confidence: 99%
“…Finally, the current study sought to define the underlying mechanism of the effect of gal-3 on NPC cells. The activation of the ERK1/2 and Akt signaling pathways is involved in the proliferation, migration, invasion, metastasis and radiosensitivity of NPC (38)(39)(40). However, whether gal-3 affects the ERK1/2 and Akt signaling pathways of NPC cell lines remains unknown.…”
Section: Expression Levels Of Gal-3 ---------------------------------mentioning
confidence: 99%
“… 48 In nasopharyngeal carcinoma, SPEN expression is also associated with lymph node metastasis and tumor stage. 49 The increased expression of SPEN was found to lead to poor prognosis, while reduced expression of SPEN suppressed migration and invasion of nasopharyngeal carcinoma. 49 These studies suggested that SPEN played an important role in tumor pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“… 49 The increased expression of SPEN was found to lead to poor prognosis, while reduced expression of SPEN suppressed migration and invasion of nasopharyngeal carcinoma. 49 These studies suggested that SPEN played an important role in tumor pathogenesis. Interestingly, both NOTCH2 and SPEN mutations were associated with lymph node metastases in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the PI3K-Akt pathway is crucial for the proliferation, migration, and invasion of NPC cells [ 41 , 42 ]. Downregulation of the SPEN gene leads to the inactivation of PI3k-Akt and c-JUN signals, thus inhibiting the migration and invasion of NPC [ 43 ]. Zhu et al revealed that inhibition of autophagy by the ANXA1 gene may promote the migration and metastasis of NPC by activation of the PI3K-Akt pathway [ 44 ].…”
Section: Discussionmentioning
confidence: 99%